Taxes: The Key to A Golden Indonesia 2045 - Alman, Fariel Zulfikar; Alman, Gabriel Choirul; Rianto, Rianto; Prakoso, Lukman Yudho; Soemantri, Asep Iwa; Prasetyo, Heru; Mujaddid, Toriq Furqon Al; Bermana, Seftiandra (PT FORMOSA CENDEKIA GLOBAL, 2024)
Taxes play a crucial role in infrastructure development, improving the quality of public services, and alleviating poverty, serving as the country's main irreplaceable income. However, optimizing tax revenues in Indonesia faces various complex and multidimensional challenges. The goal of this article is to review in depth the importance of taxes in efforts to achieve the vision of a Golden Indonesia 2045, an ambitious vision that covers various aspects of the nation's economic and social progress. This article will also examine strategies that can be implemented to increase tax revenues. It is hoped that tax revenues can be significantly optimized, thereby supporting sustainable financing of national development and realizing the vision of a Golden Indonesia 2045.